Pengaruh Profitabilitas, Solvabilitas dan Investment Opportunity Set terhadap Nilai Perusahaan dengan Kebijakan Dividen sebagai Variabel Moderasi - Rezza Anggraini; M. Hendri Yan Nyale (Forum Kerjasama Pendidikan Tinggi (FKPT), 2022)
The food and beverage industry is the most choice for investors in making investments because this sector provides basic daily needs and offers profitable prospects It has an impact on the value of the company by promising profits for investors. The increase in the amount of investment value until the end of 2020 was obtained by data that there was an increase in investors of Rp.36.6 trillion or 8.3% of the total which reached Rp. 442.76 trillion (www.katadata.co.id). With an increase in investment in a company, it can give a good impression for potential investors in interpromising the value of the company in the form of a stock price in the capital market. The increasing share price indicates a better company value, and management will increase the value of the company. This study was conducted to determine the effect of profitability, solvency and investment opportunity sets on company value with dividend policy as a moderation variable as a gap theory from previous research which is still rarely studied. The population using the Food and Beverage sub-sector companies for the 2017-2021 period amounted to 38 companies and the sample obtained was 8 companies using purposive sampling techniques. The analysis in this study used software eviews9, descriptive statistics, while hypothesis testing used multiple linear regression of panel data. The results of this study show that Profitability has a positive effect on the value of the company, while solvency and the Investment Opportunity Set have a negative effect on the value of the company. Meanwhile, profitability and the Investment Opportunity Set moderated by the dividend policy have a positive effect on the value of the company. Moderated solvency of the dividend policy negatively affects the value of the company.